Diskursus Nilai Kesakralan Perkawinan Hindu dan Fenomena Sosial Sing Beling Sing Nganten Pada Masyarakat Perkotaan di Bali - Yogiswari, Krisna S.; Maharani, Septiana Dwiputri; Nugroho, Hastanti Widy (Jurnal Penelitian Agama Hindu, 2025)
Marriage in Balinese society has traditionally been regarded as a sacred institution, deeply rooted in religious values and customary law. However, over the past few decades, significant shifts have occurred as a result of modernization, globalization, and broader social changes. One phenomenon that reflects this transformation is Sing Beling Sing Nganten, a vernacular expression increasingly circulated in contemporary Balinese discourse. The phrase refers to the social tendency wherein a couple formalizes their marriage only after the bride is already pregnant. This practice signifies a fundamental shift in the construction of marital sanctity, challenging earlier conceptions of marriage as a purely sacred and ritually-bound institution. It also suggests the emergence of a new paradigm in how marriage legitimacy is socially recognized within the Balinese context. This study employs a phenomenological approach to explore individual experiences and collective perceptions of the Sing Beling Sing Nganten phenomenon. Utilizing qualitative methods primarily in-depth interviews and participant observation, it seeks to understand how this practice is experienced, interpreted, and negotiated in everyday life, particularly by women. The central objective of this research is to analyze how Sing Beling Sing Nganten operates as a social practice that contributes to the shifting values surrounding the institution of marriage, specifically in relation to its perceived sacredness. Findings from the study indicate that this phenomenon is not merely a reflection of value transformation but also constitutes a strategic adaptation to the increasing social and economic pressures faced by individuals and families. The normalization of this practice in urban Balinese settings is shaped by the intersection of traditional cultural norms and modern pragmatic outlooks. As such, this research offers not only a phenomenological account of an evolving cultural practice but also a critical reflection on the broader transformation of value systems in contemporary Balinese society.